UPDATE OF PEDAGOGICAL VALUES IN THE PROCESS OF YOUNG TEACHERS’ PROFESSIONAL DEVELOPMENT - Striguna, Santa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
There are values in every profession that are used by its representatives in their professional activity. Such values are important to those working in education, too. The actualization of educational values is to be especially emphasized in the professional development of young teachers. Educational institutions serve as examples for modeling of acquisition and implementation of values and attitudes, for pedagogy implies values later mastered by society. In order to ensure optimal results of the process, it is important to promote the development of young teachers’ competencies for implementing innovations in acquisition of education and consolidate their functional and professional positions.